Preventing Escape of Non-Native Species from Aquaculture Facilities in Florida, Part 3: Structural Strategies - Quenton M. Tuckett; Carlos V. Martinez; Jared L. Ritch; Katelyn M. Lawson; Jeffery E. Hill (EDIS)
Non-native species sometimes escape from aquaculture facilities, but producers can prevent these potentially harmful escapes by placing barriers like screens, covers, control structures, and ponds at vulnerable points. Aquaculture producers use these structures to prevent release of non-native species in compliance with Florida Aquaculture Best Management Practices. Further, many of the structures discussed in this 9-page fact sheet are also effective in addressing and maintaining compliance with the discharge requirements of those Best Management Practices. The fact sheet provides escape prevention strategies and advice for building structures and barriers that can keep potentially harmful non-native species safely contained on aquaculture facilities. Written by Quenton M. Tuckett, Carlos V. Martinez, Jared L. Ritch, Katelyn M. Lawson, and Jeffrey E. Hill, and published by the School of Forest Resources and Conservation, Program in Fisheries and Aquatic Sciences, August 2016.